Modelluntersuchungen zum Einfluss thermohaliner und windgetriebener Zirkulationsschwanckundgen auf die marine CO2-Aufnahme - Thoma, Inger (2004)
The aim of this study is to examine the influence of both thermohaline and wind driven circulation changes on oceanic and atmospheric CO2-concentrations. For this the biopump three- and seven-box models of Toggweiler [1999] are integrated from an interglacial into a glacial steady state and vice versa. In contrast to previous studies which concentrated on steady state situations, here the focus is on transient CO2-concentrations after a sudden change in thermohaline and wind driven circulations. In addition timescales and amplitudes of atmospheric pC02-concentrations during the transition are compared to measurements of ice core datasets.